Geopolymer high-ductility engineering composite material with tailings sand replacing quartz sand and preparation method thereof

CN123003204APending Publication Date: 2026-10-30SICHUAN AGRI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611455617.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-18
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

在基体流动度严重下降的情况下,高延性材料所必需的超高分子量聚乙烯纤维在搅拌时极易发生严重结团,无法实现均匀的三维分散

Benefits of technology

(1)本发明以全固废地聚物为胶凝体系,通过铅锌尾矿大比例乃至完全替代天然石英砂,实现了力学性能与高延性特征的协同提升。在无水泥的高碱激发环境下,体系内的三元胶凝材料(地聚物材料)与尾矿细骨料形成了致密的交联网络。该材料的第28天抗压强度高达60~95MPa,极限抗弯强度分布在15~25MPa之间,极限跨中挠度达到6~10mm,兼具可靠的高结构承载能力与优异的弯曲韧性,完全满足高韧性受弯构件在复杂应力下的变形使用需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003204A_ABST
    Figure CN123003204A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of cement materials, and particularly relates to a tailing sand substituted quartz sand geopolymer high ductility engineering composite material and a preparation method thereof. The geopolymer high ductility engineering composite material is prepared from the following components in parts by mass: geopolymer material, alkali activator, water reducing agent, retarder, ultra-high molecular weight polyethylene fiber, fine aggregate and water. The present application uses geopolymer to replace traditional cement, and uses industrial tailing sand to partially or wholly replace natural quartz sand in traditional proportioning as fine aggregate, so that the compressive strength of the geopolymer high ductility engineering composite material is distributed between 60-95 MPa, the ultimate bending strength is distributed between 15-25 MPa, the ultimate mid-span deflection reaches 6-10 mm, and the geopolymer high ductility engineering composite material has reliable compressive bearing capacity, excellent bending toughness and energy dissipation capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cement materials technology, and more particularly to a geopolymer high-ductility engineering composite material in which tailings sand replaces quartz sand and its preparation method. Background Technology

[0002] Engineered cementitious composites (ECC) have great potential for application in resilient infrastructure due to their ultra-high deformation capacity (3%-10%) and excellent crack control capabilities. However, traditional engineered cementitious composites are limited by the high cost of Portland cement and quartz sand, which are used in large quantities. In addition, the high carbon emissions from Portland cement also cause a severe environmental burden.

[0003] To achieve the dual goals of carbon reduction and solid waste resource utilization, researchers are attempting to use alkali activation technology to completely replace Portland cement with industrial or municipal solid waste in the preparation of engineered geopolymer composites (EGC). Existing life cycle assessment studies have shown that geopolymer / alkali-activated concrete typically reduces carbon emissions by approximately 40% to 80% compared to ordinary silicate cement concrete, but the specific reduction is closely related to the source of precursors, the type of alkali activator, transportation distance, and curing methods. For example, a 2024 study indicated that fly ash-silica geopolymer concrete has approximately 50% lower CO2 emissions than ordinary concrete; another 2025 study indicated that fly ash-based geopolymer concrete can reduce CO2 emissions by 67%, and slag-based geopolymer concrete by 54%; a 2026 review summarized the global warming potential reduction of geopolymer concrete relative to ordinary silicate (OPC) concrete as 16% to 90%. Therefore, geopolymer cementitious materials have considerable low-carbon advantages; however, there are several technical problems that need to be solved when the traditional ECC system is applied to the EGC system.

[0004] In the research of traditional engineering cement-based composites (ECC), there are precedents for exploring the use of industrial solid waste to partially replace natural quartz sand. For example, patent CN120987609A discloses the incorporation of a small amount of lead-zinc tailings powder (5-8%) into an ECC system based on silicate cement, utilizing its micro-aggregate filling effect to optimize the interface. However, in the field of engineering geopolymer composites (EGC), characterized by cement-free and low-carbon emissions, achieving a large-scale or even complete replacement of natural quartz sand with lead-zinc tailings faces technical barriers that cannot be simply transferred from traditional ECC experience.

[0005] The high-alkali activation environment of geopolymer systems differs fundamentally from the traditional cement hydration mechanism. In EGC systems, directly replacing inert silica sand with a large proportion of lead-zinc tailings exposes the following fatal engineering and mechanical defects: First, lead-zinc tailings are rich in highly crystalline carbonate minerals (such as calcite and dolomite). When these minerals enter the highly alkaline geopolymer activation system, they provide numerous active nucleation sites for condensation reactions, triggering an extremely strong accelerating effect. This results in an extremely narrow setting time control window for geopolymers, making the slurry prone to "flash setting," causing a precipitous drop in rheological properties and completely eliminating the operability of on-site construction. Second, unlike the smooth surface of natural silica sand, lead-zinc tailings particles have irregular morphologies, are angular, and have high water absorption, which significantly increases the internal frictional resistance and yield stress of the slurry. With severely reduced matrix fluidity, the ultra-high molecular weight polyethylene fibers, essential for high-ductility materials, are prone to severe agglomeration during stirring, making uniform three-dimensional dispersion impossible. Fiber aggregation not only introduces numerous microscopic pores and defects into the matrix, but also directly disrupts the fiber bridging effect and pseudo-strain hardening (PSH) mechanism, resulting in significantly lower flexural strength and a substantial loss of ultimate deformation capacity in composite materials. Therefore, developing a novel material formulation and process synergy scheme to overcome the problems of accelerated coagulation and rheological deterioration caused by large amounts of lead-zinc tailings in high-alkali geopolymer systems, thereby achieving solid waste resource utilization while maintaining excellent workability and high ductility mechanical properties, has extremely important engineering application value. Summary of the Invention

[0006] To address the shortcomings of existing technologies, the present invention aims to provide a geopolymer high-ductility engineering composite material. This geopolymer high-ductility engineering composite material achieves its crack strength by using a specific proportion of geopolymer material, making it lower than the bridging stress of the fibers. It also incorporates retarder and water-reducing agent to extend the initial setting speed of the geopolymer material, improving the operability of EGC molding. Furthermore, it achieves uniform three-dimensional dispersion of domestically produced ultra-high molecular weight polyethylene fibers in the matrix. Simultaneously, it utilizes lead-zinc tailings to partially or completely replace quartz sand, achieving a synergistic improvement in both mechanical properties and high-ductility characteristics.

[0007] Another objective of this invention is to provide a method for preparing geopolymer high-ductility engineering composite materials.

[0008] To achieve the above objectives, the present invention is accomplished through the following technical solutions.

[0009] A geopolymer high-ductility engineering composite material, wherein the geopolymer high-ductility engineering composite material is prepared from the following components in parts by weight: Geopolymer material: 0.95~1.05 parts; Alkali activator: 0.14~0.16 parts; Water-reducing agent: 0.011~0.15 parts; 0.0015~0.0025 parts of retarder; 0.0065~0.0110 parts of ultra-high molecular weight polyethylene fiber; Fine aggregate 0.45~0.55 parts; Water 0.28~0.33 parts; The geopolymer material is a mixture of fly ash, blast furnace slag, and silica fume, wherein the mass ratio of fly ash, blast furnace slag, and silica fume is (0.71~0.79):(0.13~0.17):(0.08~0.12). The fine aggregate is selected from a mixture of quartz sand and lead-zinc tailings or lead-zinc tailings, wherein the volume percentage of lead-zinc tailings in the fine aggregate is 20-100%.

[0010] In the above technical solution, the fly ash is grade I fly ash.

[0011] In the above technical solution, the alkaline activator includes: anhydrous sodium silicate.

[0012] In the above technical solution, the modulus of the anhydrous sodium silicate is 0.95~1.00.

[0013] In the above technical solution, the water-reducing agent is a polycarboxylate high-performance water-reducing agent.

[0014] In the above technical solution, the polycarboxylate high-performance water-reducing agent includes: polyether-type polycarboxylate water-reducing agent.

[0015] In the above technical solution, the retarder is a carbohydrate.

[0016] In the above technical solution, the carbohydrate includes sodium gluconate.

[0017] In the above technical solution, the ultra-high molecular weight polyethylene fiber has a diameter of 25 μm, a length of 12 mm, a tensile strength of 2000 MPa, an elastic modulus of 105 GPa, an elongation of 3%, and a density of 0.94 g / cm³. 3 The degree of polymerization of ultra-high molecular weight polyethylene fiber is 150,000.

[0018] In the above technical solution, the quartz sand is 40~70 mesh.

[0019] In the above technical solution, the main components of the lead-zinc tailings include calcite, dolomite, quartz and mica; the particle size is ≤0.12mm.

[0020] In the above technical solution, the preferred volume percentage content of lead-zinc tailings in fine aggregate is 60-100%.

[0021] The preparation method of the above-mentioned geopolymer high ductility engineering composite material includes the following steps: Step 1: Mix the geopolymer material, alkali activator, retarder and fine aggregate evenly under low speed stirring to obtain a mixture; add water-reducing agent and water dropwise to the mixture, continue low speed stirring after the addition is completed, then stir at high speed until the mixture is evenly mixed, add ultra-high molecular weight polyethylene fiber after stirring, and continue high speed stirring to evenly disperse the ultra-high molecular weight polyethylene fiber to obtain the mixture material. Step 2: Place the mixture in a mold, vibrate to release air, let stand, demold to obtain the composite material, seal the composite material, and cure it to obtain the geopolymer high ductility engineering composite material.

[0022] In the above technical solution, a planetary cement mortar mixer is used for preparation.

[0023] In step 1, the geopolymer material, alkali activator, retarder and fine aggregate are mixed and stirred at low speed for 1 to 2 minutes until uniform; After the addition is complete, continue stirring at low speed for 1-2 minutes, then stir at high speed for 1-2 minutes until the mixture is homogeneous. Continue stirring at high speed for 3-4 minutes to ensure uniform dispersion of ultra-high molecular weight polyethylene fibers.

[0024] In step 1, the low-speed setting has a self-rotation rate of 135~145 r / min and a common rotation rate of 57~67 r / min; The high-speed setting has a self-rotation speed of 275~295 r / min and a common speed of 115~135 r / min.

[0025] In step 1, the specific operation of adding water-reducing agent and water is as follows: dilute the water-reducing agent with the first part of water, add the diluted water-reducing agent aqueous solution and the second part of water to the mixture, and divide the total water into the first part of water and the second part of water. According to the total water mass, the first part of water accounts for 10~20% of the total water volume percentage.

[0026] In step 2, the curing treatment specifically involves curing at a temperature of 55-65℃ and a relative humidity of ≥99% for 24 hours, followed by curing at a temperature of 18-22℃ and a relative humidity of ≥95% for 28 days.

[0027] In step 2, the vibration time is 1-2 minutes and the resting time is 24-48 hours.

[0028] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention uses a solid waste geopolymer as the cementing system, and achieves a synergistic improvement in mechanical properties and high ductility by replacing natural quartz sand with a large proportion or even completely using lead-zinc tailings. In a cement-free, high-alkali activating environment, the ternary cementing material (geopolymer material) in the system forms a dense cross-linked network with the tailings fine aggregate. The compressive strength of this material on day 28 is as high as 60~95MPa, the ultimate flexural strength is distributed between 15~25MPa, and the ultimate mid-span deflection reaches 6~10mm. It has both reliable high structural bearing capacity and excellent bending toughness, which fully meets the deformation and use requirements of high-toughness bending members under complex stress.

[0029] (2) This invention successfully overcomes the problem of dispersion and molding of high-dosage fibers in a solid waste system by synergistically regulating the rheology of the geopolymer ternary cementitious system and the admixture. Through the precise compounding of polycarboxylate high-performance water-reducing agent and retarder in a specific ratio, it not only effectively inhibits the "flash coagulation" effect of carbonate minerals in lead-zinc tailings under high-alkali environment and ensures a suitable construction operation time, but also significantly improves the yield stress of the slurry. This regulation enables domestically produced ultra-high molecular weight polyethylene fibers to achieve uniform three-dimensional dispersion in the matrix, without clumping or bleeding segregation throughout the process, fully meeting the mechanical vibration and compaction requirements of actual engineering projects.

[0030] (3) The efficient utilization and high strength retention of lead-zinc tailings in this invention stem from the dual optimization of its micro-aggregate filling and nucleation effect. Lead-zinc tailings not only effectively fill the internal micro-pores of the geopolymer hardened matrix as micro-aggregates at the physical level, improving the overall density; its rich calcite and other carbonate minerals also provide abundant nucleation sites for the geopolymer condensation reaction, accelerating the early reaction process. This dual densification effect of physical and chemical means that even under extreme working conditions where the composite material completely replaces natural quartz sand by 100%, it can still exhibit excellent compressive strength, achieving a perfect balance between the resource utilization of bulk solid waste and material performance.

[0031] (4) This invention achieves significant optimization of the micro-crack mechanism and macro-energy dissipation capacity through tailings doping and interfacial mechanical regulation. The introduction of lead-zinc tailings moderately softens the fracture toughness of the matrix and reduces the initial resistance to microcrack propagation, thereby effectively mitigating the risk of ultra-high molecular weight polyethylene fibers being hard-scraped during stress slippage. This mechanical mechanism effectively increases the number of effective fiber bridges on the main crack section, causing the specimen to exhibit extremely significant multi-microcrack cracking characteristics and pseudo-strain hardening mode during bending failure, fundamentally ensuring the ultimate ductility of the material.

[0032] (5) The preparation method of the present invention is simple, highly controllable, and the raw materials can be directly used from tailings, reducing the amount of quartz sand added and resulting in lower production costs. Attached Figure Description

[0033] Figure 1 This is a flowchart illustrating the preparation process of an embodiment of the present invention; Figure 2 The setting time is the time of the geopolymer high ductility engineering composite material prepared in Comparative Examples 1-6 of this invention; Figure 3 The compressive strength of the geopolymer high-ductility engineering composite materials prepared in Comparative Examples 2, 4 and 6 of this invention; Figure 4 The compressive strength of the geopolymer high-ductility engineering composite materials prepared in Examples 1-9 of this invention; Figure 5 The slump of the geopolymer high-ductility engineering composite materials prepared in Examples 1-9 of this invention; Figure 6 The stress-mid-span deflection curves of the geopolymer high ductility engineering composite materials prepared in Examples 1-3 of the present invention are shown, where (a) is Example 1, (b) is Example 2, and (c) is Example 3. Figure 7 The stress-mid-span deflection curves of the geopolymer high ductility engineering composite materials prepared in Examples 4-6 of the present invention are shown, where (a) is Example 4, (b) is Example 5, and (c) is Example 6. Figure 8 The stress-mid-span deflection curves of the geopolymer high ductility engineering composite materials prepared in Examples 7-9 of the present invention are shown, where (a) is Example 7, (b) is Example 8, and (c) is Example 9. Detailed Implementation

[0034] The following examples are intended to enable those skilled in the art to more fully understand the present invention, but do not limit the invention in any way.

[0035] Unless otherwise specified, the materials used in the embodiments of the present invention can be obtained commercially or prepared according to conventional methods known to those skilled in the art.

[0036] In the following embodiments, fibers are a crucial factor in achieving multi-crack propagation during the fabrication of engineered geopolymer composites (EGCs). Currently, most fibers used in EGC preparation are produced in Japan, relying on imports and incurring high costs, making EGC difficult to apply practically in engineering. This invention uses ultra-high molecular weight polyethylene fibers produced by Shiseido Corporation, with a degree of polymerization of 150,000. Specific parameters are shown in Table 1.

[0037] Table 1 Parameters of Ultra-High Molecular Weight Polyethylene Fiber

[0038] In the following embodiments, the water is local tap water from Dujiangyan.

[0039] In the following embodiments, the geopolymer material is a mixture of primary fly ash, blast furnace slag and silica fume, wherein the amount of fly ash added is 836.7 kg, the amount of blast furnace slag added is 167.3 kg, and the amount of silica fume added is 111.5 kg.

[0040] In this embodiment of the invention, the water-cement ratio (w / b) is fixed at 0.25, and the sand-cement ratio (s / b) is fixed at 0.5. Lead-zinc tailings are used to replace quartz sand by an equal volume, with three tailings replacement rates of 20%, 60%, and 100%. Simultaneously, three sets of ultra-high molecular weight polyethylene fiber volume fractions are set, with volume fractions of 1.5%, 2.0%, and 2.5%, respectively. Combining these two factors, the following embodiments 1-9 are designed.

[0041] Examples 1-9 A geopolymer high-ductility engineering composite material was prepared from the components shown in Table 2 by mass (kg): Table 2. Mix proportions of geopolymer high-ductility engineering composite materials

[0042] Preparation flow chart as follows Figure 1 As shown, the preparation method of the above-mentioned geopolymer high ductility engineering composite material includes the following steps: Step 1: According to the component mass in Table 2, place the geopolymer material, alkali activator, retarder, and fine aggregate into the mixing bowl of a JJ-5 planetary cement mortar mixer. Stir at a low speed of 140 r / min rotation and 62 r / min revolution for 2 minutes until the mixture is uniform, obtaining a mixture. Continue stirring at low speed, then dilute the water-reducing agent with 15% water, and add the diluted water-reducing agent solution and the remaining water dropwise. After the dropwise addition is completed, continue stirring at the same speed for 1 minute, then stir at a high speed of 285 r / min rotation and 125 r / min revolution for 1 minute. After stirring, manually disperse the ultra-high molecular weight polyethylene fiber, and continue stirring at high speed for 3 minutes to uniformly disperse the ultra-high molecular weight polyethylene fiber, obtaining the mixture. Step 2: Place the mixture in a 40mm×40mm×40mm mold and vibrate for 2 minutes to remove pores in the mixture and increase the density of the specimen. After degassing, place the mold containing the mixture on a horizontal surface and cover the mold surface with plastic wrap. Let it stand for 24 hours, then demold to obtain the composite material. Encapsulate the composite material with plastic film and cure it in a 60℃ high-temperature steam curing chamber for 24 hours. Then cure it in a constant temperature and humidity standard curing chamber at 20±2℃ and relative humidity ≥95% for 28 days to obtain the geopolymer high ductility engineering composite material.

[0043] Comparative Examples 1-6 In this invention, the water-cement ratio (w / b) is fixed at 0.25 and the sand-cement ratio (s / b) is fixed at 0.5. Lead-zinc tailings are used to replace quartz sand by equal volume, and six tailings replacement rates (0%, 20%, 40%, 60%, 80%, and 100%) are set, resulting in comparative examples 1-6 as follows.

[0044] A geopolymer high-ductility engineering composite material, without the addition of ultra-high molecular weight polyethylene fiber, is prepared from the components shown in Table 3 by mass (kg): Table 3 Geopolymer Matrix Mixing Proportions

[0045] The preparation methods of the geopolymer high ductility engineering composite materials of Comparative Examples 1 to 6 are basically the same as those of Example 1, except that the operation of adding ultra-high molecular weight polyethylene fibers is omitted.

[0046] Test Example 1 Setting time is not only an important engineering construction indicator, but also a core parameter reflecting internal condensation reactions, determining the feasibility of special processes, and ultimately determining mechanical properties. According to the "Test Methods for Standard Consistency Water Requirement, Setting Time, and Soundness of Cement," when preparing comparative examples 1-6, the initial setting time and final setting time of comparative examples 1-6 were determined using a Vicat apparatus. Timing began from the addition of water, with initial setting time measured every 5 minutes; a needle penetration of 4mm ± 1mm ​​was considered initial setting. Final setting time was measured every 15 minutes; a needle penetration of 0.5mm or no mark left by the annular attachment was considered final setting. The results are as follows: Figure 2 As shown.

[0047] Depend on Figure 2 It can be seen that as the amount of lead-zinc tailings added increases, the setting time decreases significantly. This is due to the difference in the surface of the two fine aggregates. Pure quartz sand has an extremely smooth surface and is highly chemically inert, offering almost no promotion to the formation of alkali-activated hydration products. In contrast, lead-zinc tailings are rich in highly crystalline calcite and dolomite, providing carbonate minerals for the alkali-activated reaction, accelerating the hydration reaction, and significantly advancing the initial and final setting times.

[0048] Test Example 2 The compressive strength of the geopolymer high-ductility engineering composites prepared in the above examples and comparative examples after 28 days of curing was measured on day 28.

[0049] According to the ISO standard for testing the strength of cement mortar, the compressive strength of Comparative Examples 2, 4, and 6 was tested using 40mm × 40mm × 40mm cubic specimens. The results are as follows: Figure 3 As shown. By Figure 3It can be seen that with the increase of lead-zinc tailings content, the compressive strength of the geopolymer high-ductility engineering composite material after 28 days of curing shows a pattern of first increasing and then decreasing. The compressive strength of Comparative Example 2 with a tailings content of 20% is 48.0 MPa, while the compressive strength of Comparative Example 4 with a tailings content of 60% is 59.3 MPa, which is an increase of 23.5% compared to Comparative Example 2. This is because lead-zinc tailings and standard quartz sand usually have significant differences in particle size distribution. Mixing them is essentially a recombination of aggregate gradation, filling pores and improving mechanical properties. In addition, when the lead-zinc tailings content is 100% (Comparative Example 6), the compressive strength is 52 MPa, which is a decrease of 12.3% compared to the case with a tailings content of 60%. This is because when the lead-zinc tailings content exceeds 60%, the large quartz sand particles that serve as the skeleton in the aggregate are greatly reduced, and the fine tailings particles slip against each other under pressure, resulting in a significant decrease in macroscopic bearing capacity.

[0050] Further tests were conducted on the compressive strength of Examples 1-9, such as... Figure 4 As shown, by Figure 4 It can be seen that the compressive strength of the high-ductility polymer engineering composites of Examples 1-9 after 28 days of curing ranged from 60 to 95 MPa, generally meeting the structural load-bearing requirements of conventional engineering. As the lead-zinc tailings replacement rate increased from 20% to 100%, and the ultra-high molecular weight polyethylene (PE) fiber content increased from 1.5% to 2.5%, the compressive strength of the polymer high-ductility engineering composites showed a gradual upward trend. This is mainly because the lead-zinc tailings powder exerted a good micro-aggregate filling effect, optimized the particle size distribution of the mixture, and effectively filled the micropores inside the matrix, thereby improving the overall density of the hardened matrix. Simultaneously, the higher PE fiber content formed a denser three-dimensional network structure within the matrix, which could more effectively play a bridging and crack-preventing role when the material was under pressure, limiting and delaying the initiation and propagation of microcracks inside the matrix, thus improving the compressive strength. Notably, the compressive strength of Example 9 (complete replacement and high fiber content) reached the highest value of 93 MPa. These excellent data fully demonstrate that completely replacing traditional quartz sand with lead-zinc tailings not only avoids significant microscopic defects but also produces a positive reinforcing effect. This material system achieves 100% resource utilization of solid waste aggregates while still possessing extremely superior and reliable compressive bearing capacity.

[0051] Test Example 3 According to the "Method for Determining the Flowability of Cement Mortar", the flowability of Examples 1-9 was tested using a jump table test. The results are as follows: Figure 5As shown, the fluidity of the mixtures in Examples 1-9 gradually decreased with the increase of ultra-high molecular weight polyethylene fiber content and tailings substitution rate. The fiber content had a more significant impact on spread. When the fiber content increased to 2.5%, a large number of fibers intertwined within the mixture to form a network structure, significantly increasing the yield stress of the slurry and leading to a substantial decrease in spread. Simultaneously, the multi-faceted shape and water absorption characteristics of the lead-zinc tailings particles further increased the internal frictional resistance of the mixture. It should be noted that even in Examples 7-9, which had the worst fluidity, the slurry maintained good encapsulation after standard mechanical vibration, with no obvious fiber clumping or water segregation observed throughout the process, indicating that the mix proportion system could meet the actual molding requirements.

[0052] Test Example 4 Geopolymer high-ductility engineering composites of Examples 1-9 were prepared using 40mm×40mm×160mm prism specimens (the 40mm×40mm×40mm mold was replaced with a 40mm×40mm×160mm prism mold). Bending strength was tested on day 28 according to the "Insulation Method for Testing the Strength of Cement Mortar (IOS)". Figures 6-8 As shown, by Figures 6-8 It can be seen that the ultimate flexural strength of the geopolymer high-ductility engineering composites in Examples 1-9 ranges from 15 to 25 MPa, and the ultimate mid-span deflection reaches 6-10 mm. During flexural failure, the geopolymer high-ductility engineering composites all exhibit significant flexural strain hardening characteristics and a multi-crack pattern on the bottom surface. With the increase in the lead-zinc tailings substitution rate, the ultimate flexural strength of the geopolymer high-ductility engineering composites shows a slight decrease. This is mainly due to the micropores introduced by the lead-zinc tailings reducing the overall density of the matrix. However, it is noteworthy that this reduction in matrix strength actually "softens" the fracture toughness of the matrix, making cracks easier to initiate smoothly, and the fibers are less likely to be hard-scraped during stress slippage, thus improving the ultimate mid-span deflection of the material to some extent. The fiber content has the most significant effect on improving flexural performance. As the fiber content increases from 1.5% to 2.5%, the number of effective fiber bridges on the main crack section increases, and the flexural strength and ultimate deformation capacity of the specimens are significantly improved. Even in Examples 7-9, which use 100% tailings replacement, excellent bending toughness and energy dissipation levels are still observed, indicating that the mix proportion system can fully meet the deformation requirements of high-toughness bending components.

[0053] The above embodiments are merely preferred embodiments of the present invention and are not intended to limit the implementation. The scope of protection of the present invention should be determined by the scope defined in the claims. Other variations or modifications can be made based on the above description. Obvious variations or modifications derived therefrom are still within the scope of protection of the present invention.

Claims

1. A geopolymer high-ductility engineering composite material, characterized in that, The geopolymer high-ductility engineering composite material is prepared from the following components in parts by weight: Geopolymer material: 0.95~1.05 parts; Alkali activator: 0.14~0.16 parts; Water-reducing agent: 0.011~0.15 parts; 0.0015~0.0025 parts of retarder; 0.0065~0.0110 parts of ultra-high molecular weight polyethylene fiber; Fine aggregate 0.45~0.55 parts; Water 0.28~0.33 parts; The geopolymer material is a mixture of fly ash, blast furnace slag, and silica fume, wherein the mass ratio of fly ash, blast furnace slag, and silica fume is (0.71~0.79):(0.13~0.17):(0.08~0.12). The fine aggregate is selected from a mixture of quartz sand and lead-zinc tailings or lead-zinc tailings, wherein the volume percentage of lead-zinc tailings in the fine aggregate is 20-100%.

2. The geopolymer high-ductility engineering composite material according to claim 1, characterized in that, The water-reducing agent is a polycarboxylate high-performance water-reducing agent; the retarder is a carbohydrate.

3. The geopolymer high-ductility engineering composite material according to claim 2, characterized in that, The fly ash is Grade I fly ash; The alkali activator includes: anhydrous sodium silicate; the polycarboxylate high-performance water-reducing agent includes: polyether-type polycarboxylate water-reducing agent; the carbohydrate includes: sodium gluconate.

4. The geopolymer high-ductility engineering composite material according to claim 3, characterized in that, The modulus of the anhydrous sodium silicate is 0.95~1.

00.

5. The geopolymer high-ductility engineering composite material according to claim 1, characterized in that, The main components of the lead-zinc tailings include calcite, dolomite, quartz and mica; the particle size of the lead-zinc tailings is ≤0.12mm.

6. The geopolymer high-ductility engineering composite material according to claim 1, characterized in that, Quartz sand is 40-70 mesh.

7. The method for preparing the geopolymer high-ductility engineering composite material according to any one of claims 1 to 6, characterized in that, Includes the following steps: Step 1: Mix the geopolymer material, alkali activator, retarder and fine aggregate evenly under low speed stirring to obtain a mixture; add water-reducing agent and water dropwise to the mixture, continue low speed stirring after the addition is completed, then stir at high speed until the mixture is evenly mixed, add ultra-high molecular weight polyethylene fiber after stirring, and continue high speed stirring to evenly disperse the ultra-high molecular weight polyethylene fiber to obtain the mixture material. Step 2: Place the mixture in a mold, vibrate to release air, let stand, demold to obtain the composite material, seal the composite material, and cure it to obtain the geopolymer high ductility engineering composite material.

8. The preparation method according to claim 7, characterized in that, The curing process is as follows: cure for 24 hours at a temperature of 55~65℃ and a relative humidity of ≥99% steam, and then cure for 28 days at a temperature of 18~22℃ and a relative humidity of ≥95% steam.

9. The preparation method according to claim 7, characterized in that, The low-speed setting has a self-rotation rate of 135~145 r / min and a common rotation rate of 57~67 r / min; The high-speed setting has a self-rotation speed of 275~295 r / min and a common speed of 115~135 r / min.

10. The preparation method according to claim 7, characterized in that, The vibration time is 1-2 minutes, and the resting time is 24-48 hours.

Citation Information

Patent Citations

  • High-ductility cement-based composite material based on lead-zinc tailings as well as preparation method and application of high-ductility cement-based composite material

    CN120987609A